2009
DOI: 10.1007/s00125-009-1264-4
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial reactive oxygen species generation in obese non-diabetic and type 2 diabetic participants

Abstract: Aims/hypothesis The aim of this study was to measure mitochondrial reactive oxygen species (ROS) production directly from skeletal muscle biopsies obtained from obese insulin-resistant non-diabetic and type 2 diabetic participants. Methods Ten lean healthy, ten obese non-diabetic and ten type 2 diabetic participants received a euglycaemichyperinsulinaemic clamp to measure whole body insulin sensitivity. Mitochondria were isolated from skeletal muscle biopsies, and mitochondrial ATP synthesis and hydrogen perox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
62
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 33 publications
6
62
1
Order By: Relevance
“…Human studies have shown that obesity and high-fat diet increase mitochondrial hydrogen peroxide release [18]. Furthermore, a recent study showed that mitochondrial ROS release was higher in muscle of patients with type 2 diabetes than in obese controls, but similar to that observed in lean control participants [19]. Interestingly, studies have also shown that a transient physiological increase in ROS may be essential for a training-induced increase in insulin sensitivity in type 2 diabetes patients [20] and for protection against high-fat diet-induced insulin resistance in rodents [21].…”
Section: Introductionmentioning
confidence: 74%
See 4 more Smart Citations
“…Human studies have shown that obesity and high-fat diet increase mitochondrial hydrogen peroxide release [18]. Furthermore, a recent study showed that mitochondrial ROS release was higher in muscle of patients with type 2 diabetes than in obese controls, but similar to that observed in lean control participants [19]. Interestingly, studies have also shown that a transient physiological increase in ROS may be essential for a training-induced increase in insulin sensitivity in type 2 diabetes patients [20] and for protection against high-fat diet-induced insulin resistance in rodents [21].…”
Section: Introductionmentioning
confidence: 74%
“…It has also been shown that type 2 diabetes patients had significantly higher ROS release than lean participants when related to ATP production, but similar ROS release when related to mitochondrial protein [19]. Similarly to the protocol used by Abdul-Ghani et al [19], ROS rot was determined in the presence of rotenone, which inhibits the unphysiological backflow of electrons from complex II to complex I. The fate of the electrons is therefore: (1) to be donated to oxygen, forming water in complex IV; or (2) to be donated to oxygen, forming superoxide in complex III.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations